Host preference and host colonization of the Asian long-horned beetle, Anoplophora glabripennis (Coleoptera Cerambycidae), in Southern Europe. Issue 3 (4th March 2016) - Faccoli, M.; Favaro, R.
Abstract: The Asian long-horned beetle (ALB), Anoplophora glabripennis (Motschulsky), is a highly polyphagous invasive pest with a broad range of host species, but showing relevant differences between infestation areas. Host preference and host colonization (female fecundity, egg and larval survival) were assessed in a population in Northern Italy by choice and no-choice experiments conducted in both field and laboratory conditions. During 5 years of field observations, ALB was found to infest seven genera of trees: Acer, Aesculus, Betula, Populus, Prunus, Salix and Ulmus . However, Acer, Betula, Ulmus and Salix resulted to be the preferred hosts corresponding to 97.5% (1112) of the 1140 infested trees. In both laboratory and field trials carried out on these four host genera, no-choice experiments recorded the highest host colonization of A. glabripennis on Acer trees, with the highest number of laid eggs and the lowest egg and larval mortality. Ulmus and Salix showed a lower number of laid eggs during laboratory choice test, but egg and larval mortality had mean values similar to Acer . On the contrary, despite the high number of Betula trees felled during the eradication plan carried out in the infestation area, this tree species showed the lowest beetle suitability in terms of number of laid eggs and insect survival. An overestimation of the number of infested Betula occurring during the tree survey may explain the discordance between high number of infested Betula and low beetle suitability. Instead, the large number of infested Acer recorded in the field was probably due to the high abundance of these trees occurring in parks and gardens within the infestation area and to the low adult dispersal of A. glabripennis . Overall, results from this study confirm that host species affects both beetle colonization and breeding performance. The study shows ALB host preference and host suitability varying between tree species, suggesting an ALB acceptance even of sub-optimal hosts.